2014
DOI: 10.1111/jpm.12151
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an educational mental health intervention on adolescents' perceptions of mental illness

Abstract: Nowadays, in many countries, mental health care is primarily community based. Community perceptions of mental illness are an essential issue for the quality of life of people with mental health problems and the promotion of mental health in general. The aim of this study was to explore adolescents' perceptions of mental illness and to examine the extent to which those perceptions changed after an educational mental health intervention. The data were collected twice, before and after the educational mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(43 reference statements)
0
12
0
1
Order By: Relevance
“…The third theme apparent within eight studies was relating to providing the participants with an increased knowledge of MH and illness and changing negative attitudes and beliefs. Four authors (Economou et al., ; Essler, Arthur, & Stickley, ; Rickwood et al., ; Sakellari, Sourander, Kalokerinou‐Anagnostopoulou, & Leino‐Kilpi, ) reported that a psycho‐educational intervention increased knowledge of MH. Economou et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third theme apparent within eight studies was relating to providing the participants with an increased knowledge of MH and illness and changing negative attitudes and beliefs. Four authors (Economou et al., ; Essler, Arthur, & Stickley, ; Rickwood et al., ; Sakellari, Sourander, Kalokerinou‐Anagnostopoulou, & Leino‐Kilpi, ) reported that a psycho‐educational intervention increased knowledge of MH. Economou et al.…”
Section: Resultsmentioning
confidence: 99%
“…(), Sakellari et al. () and Ashdown and Bernard (), Whitcomb and Merrell () all used samples that were relatively small and therefore, it should be recognised that it is difficult to generalise their results to the wider population. High levels of attrition was also an issue for four of the included 29 studies (Barnes et al., ; Collins et al., ; Kimber et al., ; King et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…When considering the high rate of depression and suicide rate among Korean adolescents, mental health nurses working in schools and community centres should implement multidimensional interventions considering both mental health promotion and at-risk HRBs (Katon et al, 2010). It would be helpful to apply school-based programmes strengthening adolescents' capacity such as positive self-esteem and coping skills, and cooperating parent participation and peer supports through promoting feeling of togetherness (Onnela, Vuokila-Oikkonen, Hurtig, & Ebeling, 2014;Sakellari, Sourander, Kalokerinou-Anagnostopoulou, & Leino-Kilpi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Korean policymakers should develop population-level policy and foster environments that support families, schools and communities in addressing HRBs (Atilola et al, 2014;Sakellari et al, 2014). It would be required early identification of poor mental health and multiple HRBs, and rapid referral system to specialized health care for adolescents (Sakellari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation